Warming Climates, Changing Forests: Temperature Tolerances of Trees and Carbon Dynamics in Northeastern Temperate Forests - Patterson, Angelica E (Consilience, 2013)
Extensive botanical surveys and long term plots have shown that since the early 1930’s, Black Rock Forest, located in the Hudson Highlands of New York, three tree species were extirpated and seven were gained. These results are consistent with a warming climate and suggest the Hudson River Valley may be an important location to study the effects of climate change on Northeastern forests. Classic global vegetation and species distribution models primarily use species presence/absence or presence only distribution with preferred environmental parameters to predict range distributions of plant communities under increasing CO2 regimes, and thus climate warming. Although these models have begun to incorporate physiological data (photosynthesis, stomatal response, and respiration), they lack a sophisticated parameterization of species-specific physiological characteristics and complex interactions within plant communities. More experimentation is necessary to validate assumptions regarding the mechanisms behind tree species responses to climate change and narrow the variability of model outputs. During the summer of 2012, I explored the physiological mechanisms for species tolerance to increasing temperatures and considered the potential effects on the carbon storage capacity of forest trees under the predicted warmer climates of the coming century.